The effects of a prospective sink environmental hygiene intervention on Pseudomonas aeruginosa and Stenotrophomonas maltophilia burden in hospital sinksResearch in context - Erin P. Newcomer; Caroline A. O'Neil; Lucy Vogt; David McDonald; Candice Cass; Meghan A. Wallace; Tiffany Hink; Francesca Yerbic; Carol Muenks; Rebecca Gordon; Olivia Arter; Henry Stewart; et al. (EBioMedicine)
Summary: Background: Opportunistic premise plumbing pathogens (OPPPs) can establish reservoirs in hospital plumbing and cause healthcare associated infections (HAIs). There is currently no widely accepted protocol for sink drain cleaning to reduce OPPP burden. Methods: We implemented a sink cleaning intervention in 12 intensive care unit (ICU) rooms. At low frequency (1×/week) and high frequency (5×/week) intervals, we wiped sink surfaces with 10% bleach wipes and pumped a foamed preacid disinfectant into sink drains. We also maintained untreated rooms (0×/week). We used E-swabs to sample sink drains and surrounding surfaces during one baseline, two intervention, and two post-intervention periods over 23 months. Samples were selectively cultured for bacterial growth and antimicrobial resistant organism (ARO) isolation. We conducted whole-genome sequencing (WGS) on Pseudomonas spp. and Stenotrophomonas spp. isolates to track impacts on reservoirs over time. We also collected and analysed clinical isolates from patients occupying the study rooms and information about HAIs that occurred. Findings: The intervention reduced the proportion of sink drains yielding Gram-negative bacteria by up to 85% (95% CI: 56–114%) in high frequency rooms versus the baseline period, but this was not significant in low frequency rooms. It also reduced the proportion of sink drains yielding Pseudomonas spp. and Stenotrophomonas spp. by up to 100% (95% CI: 79–121%) and 95% (95% CI: 65–125%) versus the baseline period in high frequency rooms and up to 71% (95% CI: 50–92%, p < 0.001) and 66% (95% CI: 27–105%, p < 0.05) in low frequency rooms, respectively. WGS showed strains of Pseudomonas aeruginosa and Stenotrophomonas maltophilia that colonised sink drains for over 3 years across two studies. Following the intervention periods, P. aeruginosa reservoirs were replaced with new strains, while S. maltophilia reservoirs returned with the same strains. Interpretation: This environmental hygiene intervention may be effective in reducing the burden of OPPPs in hospital sinks. Funding: Agency for Healthcare Research and Quality (R01HS027621), National Institute of Allergy and Infectious Diseases (U01AI123394, 1K23AI137321), Barnes-Jewish Hospital Foundation (5102), Washington University Institute of Clinical and Translational Sciences (4462) from the National Center for Advancing Translational Sciences (UL1TR002345).